Student Surveys: Measuring the Relationship between Satisfaction and Engagement - Camille Kandiko Howson; Frederico Matos (MDPI AG, 2021)
This study explores the relationship between satisfaction and engagement survey items through an institutionally based survey, drawing on the two largest higher education student experience surveys in the world. The UK-based National Student Survey (NSS) was designed to inform student choice and drive competition and the US-based National Survey of Student Engagement (NSSE) was developed to provide actionable data for institutional enhancement. Comparing these surveys leads to a critical review of how such data can be used for policy decisions and institutional enhancement. The Institutional Experience Survey thus draws on findings from a survey of 1480 non-final year undergraduate students in a research-intensive UK university. Those who reported higher levels of engagement, measured across 17 engagement benchmarks, also reported significantly higher levels of satisfaction. Results are used to discuss the application of engagement-based surveys in the UK, compared to satisfaction-based surveys, and the benefits and challenges of both approaches. Conclusions are made about the usefulness of nationally standardised experience surveys, the different outcome goals of engagement and satisfaction, such as responsibility for learning and change, audience and results and lessons for other countries looking to measure the student experience. The paper highlights the need for a shift in perspective in relation to the role of student surveys in determining national and institutional policy from a student-as-customer approach to one that sees students and institutions as co-responsible for learning and engagement.